Site selection assessment of vacant campus space transforming into daily care centers for the aged - Juan, Yi-Kai; Hsu, Yi-Chu; Chang, Yen-Ping (International Journal of Strategic Property Management, 2021)
Taiwan is facing the dual severe social problems of an aging population coupled with a low birth rate. Aging has given rise to an urgent need for future long-term care and daytime care, while the low birth rate has led to a large number of vacant classrooms on campus. The government is actively developing the policy of reusing idle campuses as daily care centers for the aged. However, the implementation of this policy lacks a set of complete evaluation mechanisms. The purpose of this study was to propose a three-stage site selection assessment model to construct site selection assessment indicators, construct indicator weights using the analytic hierarchical process (AHP), and rank the campuses most suitable for transformation into daily care centers for the aged according to the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The results showed that the convenience of family members’ transportation, access to medical treatment, service life of school buildings, barrier-free spaces, and ventilation condition are all key factors regarding the future transformation of vacant campus spaces into daily care centers. The assessment model could provide a reference to accelerate the decision-making benefits regarding the sustainable reuse of idle campus spaces.First published online 19 November 2020